Bowel mucosal necrosis and perforation following administration of calcium polystyrene sulfonate (Kalimate) in patients with hyperkalemia: Report of two cases. Issue 2 (26th November 2020) - Shen, Chang‐Ping; Chen, Li‐Wei; Chang, Liang‐Che; Jhu, Jian‐Min; Wang, Chih‐Yuan
Abstract: Hyperkalemia is a common problem in patients with acute or chronic kidney disease. Cation exchange resins, such as calcium polystyrene sulfonate (Kalimate) or sodium polystyrene sulfonate (Kayexalate), are frequently administered orally or rectally to correct hyperkalemia. Kalimate/Kayexalate administration has been reported to induce gastrointestinal injury. We report two cases of colonic necrosis and bowel perforation following Kalimate adminstration. A review of past literature pertaining to Kalimate/Kayexalate‐associated complications was performed.